1000 Kikuyu proverbs : - Barra, G. (Kenya Literature Bureau, 1991)
African love and traditions have over the years been kept alive through oral transmission from generation to generation. In 1000 Kikuyu proverbs, each proverb is printed in Kikuyu, then translated directly into English. In most cases the English equivalents of these Kikuyu proverbs have been given, in bold letters. This book will makle very good readership and act as an excellent source of material for Oral Literature -- Présentation de l'éditeur.